Pengembangan Aplikasi Android Pada UKM Basket Universitas Diponegoro - Adrian Putranda Rispurwadi; R. Rizal Isnanto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2016)
Until now, Diponegoro University has become one of the most favored State University for High School students to proceed their study. So far, there hasn’t been any information system for basketball student organization in Diponegoro University such as mobile device application that provides information, field location, and reminder for the basketball practice. Based on this concern, an application for the information system must be made on Android Operation System. Design of mobile information system for basketball student organization in Diponegoro University based android, a client server application created by using theJava, PHP, jQuery and MySQL for database. The intake of latitude and longitude coordinate will utilize the GPS feature on the mobile device and will be displayed on Google Maps API. JSON will collect the data of schedules into the mobile device, continued to recieve dialog alert and broadcast reciever for the alarm feature. The result of this design is realization of a application that able to search location of a basketball field based on android system, equipped with features that can help user to find the field and alarm to remind them of practice time. This design is also used to introduce android application developers using the Global Positioning System functions for user navigation.